2020
DOI: 10.1177/1055665620913780
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Mandibular Morphology in Pierre Robin Sequence to Optimize Mandibular Distraction Osteogenesis

Abstract: Background: Mandibular distraction osteogenesis (MDO) is the primary surgical intervention to treat airway obstruction in Pierre Robin sequence (PRS). Current morphologic studies of PRS mandibles do not translate into providing airway management decisions. We compare mandibles of infants with nonsyndromic PRS to controls characterizing morphological variances relevant to distraction. We also examine how morphologic measurements and airway grades correlate with airway management. Methods: Patients with PRS unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
2
0
2
Order By: Relevance
“…Notably, the improvement in DLG did not always correlate with the severity of micrognathia when classified by measuring maxillomandibular discrepancy on computed tomography. Similar observations have been made in the literature for baseline mandibular characteristics and laryngoscopic findings (Volk et al, 2020). Most recently, Heffernan et al (2019) reviewed 22 infants with RS who underwent MDO at Boston Children's Hospital.…”
Section: Discussionsupporting
confidence: 71%
“…Notably, the improvement in DLG did not always correlate with the severity of micrognathia when classified by measuring maxillomandibular discrepancy on computed tomography. Similar observations have been made in the literature for baseline mandibular characteristics and laryngoscopic findings (Volk et al, 2020). Most recently, Heffernan et al (2019) reviewed 22 infants with RS who underwent MDO at Boston Children's Hospital.…”
Section: Discussionsupporting
confidence: 71%
“…A Hotelling test again revealed that the ramus was the mandibular structure most affected by changes in Sox9 dosage ( Figure 6 N). Although milder, these alterations in mandibular ramus morphology are reminiscent of phenotypes observed in PRS patients, as quantified by a number of studies ( Bienstock et al., 2016 ; Chen et al., 2015 ; Chung et al., 2012 ; Suri et al., 2010 ; Susarla et al., 2017 ; Volk et al., 2020 ; Zellner et al., 2017 ; Table S4 ; Figure S6 C). Finally, to address whether enhancer knockout results in failure to thrive, we weighed pups up to weaning age (P20–P25) and detected a reduction in weight gain for mEC1.45 knockout animals ( Figure 6 O).…”
Section: Resultsmentioning
confidence: 89%
“…15,18 Multiple studies to date have characterized the RS mandible, both pre-and post-distraction, but the majority have provided only short and intermediate-term data. [15][16][17]22,23 The present study adds to this growing body of literature by providing novel long-term morphologic data on the distracted and conservatively managed RS mandible.…”
Section: Discussionmentioning
confidence: 87%